Agent environments for multi-agent systems IV : 4th international workshop, E4MAS 2014 - 10 years later, Paris, France, May 6, 2014, revised selected and invited papers /: 4th international workshop, E4MAS 2014 - 10 years later, Paris, France, May 6, 2014, revised selected and invited papers. (2015) - Unknown
No abstract available